Study Of The Impact Of Nutrition Consultants\' Educational Level On Their Strategic Analysis About The Entrepreneurial Opportunities - Pedram Yazdani; Hamidreza Rezaeian Zadeh; Mohammadreza Meigounpoory (Tehran University of Medical Sciences, 2012)
Background and Aim: Nowadays, because of the intense competition between nutrition consultants and rapid changes in patients' demands for nutrition counseling, application of the concepts such as "Entrepreneurial Opportunities Recognition" in this field seems unavoidable. One of the most commonly used methods for recognition of entrepreneurial opportunities is "Strategic Analysis of External Environment". Present survey has been conducted in order to study the impact of nutrition consultants' educational level on their strategic analysis about entrepreneurial opportunities. Materials and Methods: This analytical survey was implemented based on the data (nutrition consultants' educational levels and their responses regarding the supply and demand for nutrition counseling services) which was collected during a previous study entitled ((Analysis of supply and demand trends in the field of diabetes nutrition counseling: A basic step towards identifying the entrepreneurial opportunities for nutrition consultants)). Also, ((Spearman's correlation test)) and ((GLM multivariate test)) were performed for the analysis of aforementioned data. Results: Both statistical tests showed that nutrition consultants' educational levels (including 1- Bachelor of Science and 2- Master of Science and PhD) had significant relationship with two-thirds of their comments. Conclusion: Nutrition consultants' educational level has a relative impact on their strategic analysis about the entrepreneurial opportunities.